Ophiocordyceps asiana and Ophiocordyceps tessaratomidarum (Ophiocordycipitaceae, Hypocreales), two new species on stink bugs from Thailand - Khao-ngam, Srikhun; Mongkolsamrit, Suchada; Rungjindamai, Nattawut; Noisripoom, Wasana; Pooissarakul, Wuttikorn; Duangthisan, Jomsurang; Himaman, Winanda; Luangsa-ard, Janet Jennifer (My University, 2021)
Two new Ophiocordyceps species from Thailand, which belong to Ophiocordyceps nutans species complex and attack adult and nymph of stink bugs, are described: Ophiocordyceps asiana and O. tessaratomidarum. Molecular phylogenetic analyses of ITS and a combined sequence data of LSU, RPB1 and TEF1 revealed that these two new species are distinct from other known species in Ophiocordyceps nutans species complex. Based on the findings on morphological studies, they further support the naming of these two novel species. Ophiocordyceps asiana is parasitic on adult and nymph stink bugs, members of Coreidae and Pentatomidae which were recorded from China, Japan and Thailand, while O. tessaratomidarum is reported from Thailand for the first time and is only found as a parasite on adult stink bug, Tessaratoma papillosa (Tessaratomidae, Hemiptera). The fertile heads of O. asiana are shorter than reported for O. tessaratomidarum, and the colours of fertile heads producing teleomorph of these two species differs from each other by having strong reddish orange or light yellowish pink in O. asiana and pale yellow in O. tessaratomidarum.
Keywords: Entomopathogenic fungi; Phylogenetics; Species complex; Stink bugs; Taxonomy